A Bill for regulating the fur trade and establishing a criminal and civil jurisdiction within certain parts of North America [electronic resource]. - Great Britain. Parliament. ([S.l. : s.n., 1821)
At head of title: 2 Geo. IV.-Sess. 1821. "Ordered by The House of Commons, to be Printed, 6 June 1821." Electronic reproduction. Mode of access: Internet. 44